Evaluation of beliefs about pain control in patients after physicaltherapy treatment - Sztandera, Paulina; Szczepanowska-Wołowiec, Beata (Journal of Education, Health and Sport, 2017)
Background and aim of study. Pain is probably the most often feeling in life, mostly it is not comfortable for people and they cannot work because of it. It is not only the symptom but the disease too. People often do not know the reason for the disease and cannot remove it from life. The purpose of the research was the evaluation of pain control and whether and how much the physiotherapy treatment influence on reducing the pain on patients. Material and methods. The study was conducted among 52 patients with pain. Evaluation of the pain was examined by pain questionnaire and BPCQ questionnaire. Intensity of the pain was evaluate by VAS scale. Results: All patients after the treatment have reduced the intensity of pain. There is no correlation between internal control measured by BPCQ and reduction of the pain. There is a correlation between influence of the doctors and chance events on pain and pain reduction. Conclusions: Physiotherapy treatment reduced intensity of the pain. If there is higher influence of doctors and chance events on the pain then reduction of the pain is higher too. There is no correlations between internal control and reduction of the pain after the treatment.